2012
DOI: 10.7763/ijapm.2012.v2.63
|View full text |Cite
|
Sign up to set email alerts
|

Integrating Geo-Electrical and Geotechnical Data for Soil Characterization

Abstract: Abstract-Precise determination of engineering properties of soil is essential for proper design and successful construction of any structure. The conventional methods for determination of engineering properties are invasive, costly and time-consuming. Electrical resistivity survey is an attractive tool for delineating subsurface properties without soil disturbance. Reliable correlations between electrical resistivity and other soil properties will enable us to characterize the subsurface soil without borehole … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
14
0

Year Published

2013
2013
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 30 publications
(18 citation statements)
references
References 16 publications
4
14
0
Order By: Relevance
“…1 and 2, moisture content and bulk density value was higher with the decrease in soil electrical resistivity value due to the presence of more water content in soil tested. This finding confirmed the past findings which indicated the moisture content value will increase with the decreasing of soil resistivity value [17]- [21]. When water was added continuously from dry soil until it reach oversaturated condition, the ease of current propagation in soil will be increased, thus producing a high to low resistivity value.…”
Section: Resultssupporting
confidence: 91%
See 1 more Smart Citation
“…1 and 2, moisture content and bulk density value was higher with the decrease in soil electrical resistivity value due to the presence of more water content in soil tested. This finding confirmed the past findings which indicated the moisture content value will increase with the decreasing of soil resistivity value [17]- [21]. When water was added continuously from dry soil until it reach oversaturated condition, the ease of current propagation in soil will be increased, thus producing a high to low resistivity value.…”
Section: Resultssupporting
confidence: 91%
“…Detailed results from all the percentage of water (1-5 %) used was given in Table I. It was found that both correlations showed a curvilinear trend in line with previous researcher findings [17] - [21]. According to Fig.…”
Section: Resultssupporting
confidence: 80%
“…According to Figures 4 -7, moisture content and bulk density value were higher with the decrement of soil electrical resistivity value due to the presence of higher water content in soil tested. This findings was in line from the previous findings which indicates that the moisture content value will increase with the decrement of soil resistivity value (Abidin et al 2014c;Cosenza et al 2006;Ozcep et al 2010;Rinaldi & Cuestas 2002;Siddiqui & Osman 2012) represented by general relationship of ERV ∞ 1/w. When water was added continuously from dry condition until it reached saturated and oversaturated condition, the ease of current propagation in soil will be increased, thus produced high to low resistivity value.…”
Section: Electrical Resistivity Value (Erv)supporting
confidence: 82%
“…Electrical electrical sounding or 2D survey is carried out at the drill hole location BH-01, BH-02, BH-03 and BH-04, use simple equipment and accessories in obtaining electrical resistivity values, e.g., DC power sources, insulated cables, steel electrodes. Electric sounding is performed using a Wenner electrode configuration with a 3 m electrode distance (Siddiqui and Osman, 2012).…”
Section: Methodsmentioning
confidence: 99%